Information and Communication Technology, Energy Consumption and Financial Development in Africa - Tsaurai, Kunofiwa (International Journal of Energy Economics and Policy, 2020)
The study investigated the impact of information and communication technology (ICT) and energy consumption on financial development in Africa using dynamic Generalised Methods of Moments (GMM) with secondary annual data spanning from 2001 to 2015. Literature is unanimous that ICT and energy consumption separately contributes towards financial development although there are so far scarce case studies which focused on the African continent. When domestic credit to private sector (% of GDP) was used as a measure of financial development, ICT and energy consumption were found to had a non-significant negative influence on financial development, a finding that contradicts majority of literature on the subject matter. When broad money (% of GDP) was used as a proxy of financial development, both ICT and energy consumption had a significant positive effect on financial development. The finding generally resonates with Kirmani et al (2015) whose study argued that ICT increases efficiency, reliability, effectiveness, performance and other characteristics of modern-day commercial operations through the way transactions are catered for in any financial system. African nations are therefore urged to increase their use of modern ICT technology and increase energy consumption in order to boost financial development. Future studies can also focus whether ICT and energy consumption influence financial development through other channels such as economic growth, among others. Keywords: Information and Communication Technology; Energy Consumption; Financial Development; Africa JEL Classifications: N7, Q4, E44, O55 DOI: https://doi.org/10.32479/ijeep.8721